N-doped graphene quantum dots incorporated cobalt ferrite/graphitic carbon nitride ternary composite for electrochemical overall water splitting. (26th January 2023) - Reghunath, B Shalini; Rajasekaran, Sruthi; Devi K R, Sunaja; Pinheiro, Dephan; Jaleel UC, Jadan Resnik
Abstract: Multicomponent electrocatalysts containing carbon supports play a crucial role in influencing the hydrogen and oxygen evolution reactions which enhance the total water splitting. Herein, we report a ternary composite with cobalt ferrite, graphitic carbon nitride, and N-doped graphene quantum dots prepared via hydrothermal technique. The purity of the samples is established by carrying out various characterization methods. The intrinsic characteristics of the obtained materials are investigated by employing electrocatalytic processes in an alkaline media toward hydrogen and oxygen evolution reactions. Cobalt ferrite/graphitic carbon nitride/N doped graphene quantum dots electrocatalyst demonstrates a very low overpotential towards hydrogen evolution reaction of 287 mV at a constant 10 mA cm −2 current density in 1.0 M KOH. Tafel slope and Rct values generated are 94 mV dec −1 and 0.86 cm 2, respectively. Oxygen evolution reaction studies reveal an overpotential of 445 mV at 10 mA cm −2 with a Tafel slope of 69 mV dec −1 . Finally, the cell potential needed for the cobalt ferrite/graphitic carbon nitride/N doped graphene quantum dots electrode to achieve 10 mA cm −2 in total water splitting is only 2.0 V while displaying long-term stability. Graphical abstract: Image 1 Highlights: A ternary composite of CoFe2 O4 /gCN/NGQDs is prepared via hydrothermal method. Intrinsic features of electrocatalytic active sites are studied for overall water splitting. CGD attains 287 and 445 mV for HER and OER at η10, respectively. CGD ∥ CGD electrolysis system, requires only 2.0 V @ 10 mA cm −2 .